2007
DOI: 10.1007/s00024-007-0263-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Scattering Seismic Attenuation in Southwestern Anatolia

Abstract: The intrinsic dissipation and scattering attenuation in southwestern (SW) Anatolia, which is a tectonically active region, is studied using the coda waves. First the coda quality factor (Q c ) assuming single scattering is estimated from the slope of the coda-wave amplitude decay. Then the Multiple Lapse Time Window (MLTW) analysis is performed with a uniform earth model. Three non-overlapping temporal data windows are used to calculate the scattered seismic energy densities against the source-receiver distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the 2 4 Hz band, scattering is strong in Hokkaido and northern Honshu, but it is weak in western Japan, and especially weak in Shikoku. 1 Kanto-Tokai, Japan (Fehler et al 1992), 2 Long Valley, California (Mayeda et al 1992), 3 Central California (Mayeda et al 1992), 4 Hawaii (Mayeda et al 1992), 5 Japan (Hoshiba 1993), 6 Southern California (Jin et al 1994), 7 Northern Greece (Hatzidimitriou 1994), 8 Southern Spain, < 170 km (Akinci et al 1995), 9 Southern California (Adams and Abercrombie 1998), 10 Northeastern Venezuela (Ugalde et al 1998), 11 Eastern Turkey (Akinci andEyidogan 2000), 12 Southern Apennines Bianco et al (2002), 13 South Central Alaska (Dutta et al 2004), 14 Southern Netherlands (Goutbeek et al 2004), 15 Northeastern Colombia (Vargas et al 2004), 16 Northeastern Italy (Bianco et al 2005), 17 Southern Sicily (Giampiccolo et al 2006), 18 Southern Anatolia (Sahin et al 2007), 19 Japan (average) (Carcolé and Sato 2010), 20 Southern central Andes (D <40 km) (Badi et al 2009), 21 Southern central Andes (40 km < D < 210 km) (Badi et al 2009), 22 Southeastern South Korea (Lee et al 2010) In the 8 16 Hz band, scattering is strong in Honshu; however, it is weak in Shikoku.…”
Section: Mltwa In Japanmentioning
confidence: 99%
“…In the 2 4 Hz band, scattering is strong in Hokkaido and northern Honshu, but it is weak in western Japan, and especially weak in Shikoku. 1 Kanto-Tokai, Japan (Fehler et al 1992), 2 Long Valley, California (Mayeda et al 1992), 3 Central California (Mayeda et al 1992), 4 Hawaii (Mayeda et al 1992), 5 Japan (Hoshiba 1993), 6 Southern California (Jin et al 1994), 7 Northern Greece (Hatzidimitriou 1994), 8 Southern Spain, < 170 km (Akinci et al 1995), 9 Southern California (Adams and Abercrombie 1998), 10 Northeastern Venezuela (Ugalde et al 1998), 11 Eastern Turkey (Akinci andEyidogan 2000), 12 Southern Apennines Bianco et al (2002), 13 South Central Alaska (Dutta et al 2004), 14 Southern Netherlands (Goutbeek et al 2004), 15 Northeastern Colombia (Vargas et al 2004), 16 Northeastern Italy (Bianco et al 2005), 17 Southern Sicily (Giampiccolo et al 2006), 18 Southern Anatolia (Sahin et al 2007), 19 Japan (average) (Carcolé and Sato 2010), 20 Southern central Andes (D <40 km) (Badi et al 2009), 21 Southern central Andes (40 km < D < 210 km) (Badi et al 2009), 22 Southeastern South Korea (Lee et al 2010) In the 8 16 Hz band, scattering is strong in Honshu; however, it is weak in Shikoku.…”
Section: Mltwa In Japanmentioning
confidence: 99%
“…The attenuation properties of the east Anatolian plate boundary are similar to those in the other side of Anatolia. In western and southwest Anatolia, numerous studies have been carried out to found out the attenuation of seismic waves in the crust (AKıNCı et al, 1994;HORASAN and BOZTEPE-GÜ NEY, 2004;SAHIN et al, 2007;SAHIN, 2008). These studies have generally found out low values of Q c for tectonically and seismically active regions.…”
Section: Introductionmentioning
confidence: 99%